Impact of the More Doctors Program on hospitalizations due to conditions seen in primary care - Martins, Adenísio Vicente (2022)
Introduction: In Brazil, one of the main challenges that Family Health Strategy (ESF) has been facing is the high turnover of professionals, especially family and community doctors. Thus, the More Doctors Program (MDP) emerged to meet the shortage of medical professionals in Brazilian regions, to ensure quality care in primary health care. Objective: To analyze the effectiveness of the More Doctors Program (MDP) based on hospitalizations for conditions seen in primary care before and after implementation. Methods: Ecological time series study, with data from 2010 to 2016, a period of three years before and after the implementation of MDP in Southwest Goiás, extracted from the hospital information system. Data tabulation was performed using TabWin3.2 and later analyzed using the Stata 15.0 program, with trend analysis using linear regression. Results: The mean hospitalization rate was statistically higher than that for primary care conditions (p<0.001). The latter was statistically higher in men (p<0.05). There was a reduction in the overall hospitalization rate for primary care-treated conditions (p<0.001) after the implementation of MDP (p<0.001). Conclusions: The results of this study suggest that the inclusion of physicians in primary health care services after the implementation of the program contributed to access to health services, by showing a tendency of the Program's actions to reduce the most significant ICSAP.